Tissue specific uptake and elimination of perfluoroalkyl acids (PFAAs) in adult rainbow trout (Oncorhynchus mykiss) after dietary exposure. (June 2015) - Falk, Sandy; Failing, Klaus; Georgii, Sebastian; Brunn, Hubertus; Stahl, Thorsten
Abstract : Graphical abstract: Highlights: Tissue specific uptake and elimination of PFAAs in adult rainbow trout. Dietary exposure via spiked food over a time period of 28 d (accumulation period). Accumulation period was followed by a 28 d depuration period (PFAA free food). Muscle, liver, kidneys, gills, blood, skin and carcass were examined individually. Estimation of tissue specific elimination half-lives for each substance. Abstract: Tissue specific uptake and elimination of perfluoroalkyl acids (PFAAs) were studied in rainbow trout ( Oncorhynchus mykiss ). Adult trout were exposed to perfluorobutane sulfonic acid (PFBS), perfluorohexane sulfonic acid (PFHxS), perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA) and perfluorononanoic acid (PFNA) via food over a time period of 28 d. In the following 28-d depuration period the fish were fed PFAA-free food. At defined sampling times four animals were removed from the experimental tank, euthanized and dissected. Muscle, liver, kidneys, gills, blood, skin and carcass were examined individually. At the end of the accumulation phase between 0.63% (PFOA) and 15.5% (PFOS) of the absolute, applied quantity of PFAAs was recovered in the whole fish. The main target organ was the liver with recovery rates between 0.11% (PFBS) and 4.01% (PFOS) of the total amount of ingested PFAAs. Perfluoroalkyl sulfonic acids were taken up more readily and had longer estimated elimination half-lives than perfluoroalkyl carboxylic acids of the same chain length. The longest estimated elimination half-lives were found to be for PFOS between 8.4 d in muscle tissue and 20.4 d in the liver and for PFNA between 8.2 d in the blood and 11.6 d in the liver.